Inducing High Temperature Shock at Onset of the Anthesis and Its Effect On Grain Quality of Wheat Cultivars - Mohammad Akmal; Rabia Goher (Turkish Journal of Agriculture: Food Science and Technology)
Uncertain heat shock by a rapid increase in temperature particularly at the critical growth stage affects plant productivity. The study aimed to assess qualitative changes in wheat grains when plant exposed to high temperature shock (HTS) at starting anthesis for limited durations (48, 72 and 96h). Selected wheat cultivars (Pirsabak-2005, Pakhtunkhwa-2015, Pakistan-2013, DN-84, P-2, P-12 and P-18) were exposed to extending HTS effective from anthesis in the field covering plants within plastic tents for a limited duration. The experiment was conducted in 2017-18 and 2018-19 at the Research Farm, the University of Agriculture Peshawar, Pakistan in a randomized complete block design, in three replications. Temperatures inside and outside plastic tents were manually noted. Two years mean data showed significant effects of HTS on the wheat grain quality. Imposed HTS for 48, 72 and 96h resulted in a reduction on grain amylose by 23, 39 and 48% and wet gluten by 16, 25 and 36%, respectively when compared with the control (i.e. no HTS). Contrary to this, as compared to the control treatment an increase noted in the grain amylopectin by 7, 11 & 17% and in the grain N-content by 13, 28 & 41% with imposing HTS extending to a duration of 48, 72 and 96h, respectively. The study concluded adverse effects of HTS at the anthesis stage on wheat grain quality disturbing amylose and amylopectin ratios, which latter on brought changes in floor structure and gluten elasticity. However, cultivar did differ to respond to the changes but have the option to choose the best one.